2023
DOI: 10.1038/s41467-023-39921-4
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes in the essential E. coli septal cell wall synthesis complex suggest an activation mechanism

Brooke M. Britton,
Remy A. Yovanno,
Sara F. Costa
et al.

Abstract: The bacterial divisome is a macromolecular machine composed of more than 30 proteins that controls cell wall constriction during division. Here, we present a model of the structure and dynamics of the core complex of the E. coli divisome, supported by a combination of structure prediction, molecular dynamics simulation, single-molecule imaging, and mutagenesis. We focus on the septal cell wall synthase complex formed by FtsW and FtsI, and its regulators FtsQ, FtsL, FtsB, and FtsN. The results indicate extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 65 publications
(112 reference statements)
2
9
0
Order By: Relevance
“…The proposed mechanism works as if the arrival of FtsN to the divisome triggers the onset of constriction even though the actual mechanism is the conformational switch of FtsA induced by FtsZ protofilament bundling. The proposed mechanism does not contradict recent single-molecule tracking data where some fraction of FtsBQL and FstIW complexes were found to move together with treadmilling FtsZ protofilaments 21,23 . These complexes can bind to mostly monomeric FtsA and follow treadmilling FtsZ protofilaments by diffusion and capture 25 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The proposed mechanism works as if the arrival of FtsN to the divisome triggers the onset of constriction even though the actual mechanism is the conformational switch of FtsA induced by FtsZ protofilament bundling. The proposed mechanism does not contradict recent single-molecule tracking data where some fraction of FtsBQL and FstIW complexes were found to move together with treadmilling FtsZ protofilaments 21,23 . These complexes can bind to mostly monomeric FtsA and follow treadmilling FtsZ protofilaments by diffusion and capture 25 .…”
Section: Discussionsupporting
confidence: 52%
“…FtsN is the last essential component to arrive at the divisome. Accordingly, it has been considered the trigger protein for cell division in E. coli 13-21 .…”
Section: Introductionmentioning
confidence: 99%
“…Many key questions remain unaddressed regarding the spatial-temporal control over sPG synthesis. For instance, past studies, including ours, show that the FtsWI and FtsQLB exist in a stable complex on both the Z and sPG tracks (16, 36). However, FtsWI/QLB and FtsN are expressed in low abundance (∼ 10s of molecules each) at septum (28, 37, 38), FtsWI/QLB join the divisome independent of FtsN (2, 7, 9, 10), and they spend most of their time on the Z-track and sPG track respectively without much free diffusion (if at all) (28, 35).…”
Section: Introductionmentioning
confidence: 73%
“…In the later simulation for Stages II and III of septum constriction, FtsN molecule numbers will evolve between 20 and 60 as septum constriction progresses (28), whereas FtsWI/QLB complex numbers will be at 20. For simplicity, the model treats FtsWI/QLB as one complex, as previous studies, including ours, showed that FtsWI and FtsQLB form a stable complex without other divisome components (16, 36). Each FtsWI/QLB complex or FtsN molecule is represented by a single circular particle of 5 nm in diameter (44–46), and they volumetrically exclude each other.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of a Cryo-EM structure of the Pseudomonas aeruginosa divisome was largely consistent with predicted protein-protein interfaces, but also revealed a global conformational change absent in structure predictions [19]. All-atom MD simulations identified a similar conformational change within 1 µs, and further predicted interactions between the core divisome and E. coli FtsN [20]. However, limitations of this MD approach, such as uncertainty in structure predictions and limited MD timescales, call for experimental validation.…”
Section: Introductionmentioning
confidence: 85%